Lajos Grendel, A modern irodalom története. Magyar líra és epika a 20. században. Pozsony, 2010, Kalligram, ss. 512 - Piotrowiak-Junkiert, Kinga (Porównania, 2012)
Lajos Grendel, A modern irodalom története. Magyar líra és epika a 20. században. Pozsony, 2010, Kalligram, ss. 512.